PEX16 contributions to peroxisome import and metabolism revealed by viable Arabidopsis pex16 mutants. Issue 7 (3rd April 2019) - Burkhart, Sarah E.; Llinas, Roxanna J.; Bartel, Bonnie
Abstract: Peroxisomes rely on peroxins (PEX proteins) for biogenesis, importing membrane and matrix proteins, and fission. PEX16, which is implicated in peroxisomal membrane protein targeting and forming nascent peroxisomes from the endoplasmic reticulum (ER), is unusual among peroxins because it is inserted co‐translationally into the ER and localizes to both ER and peroxisomal membranes. PEX16 mutations in humans, yeast, and plants confer some common peroxisomal defects; however, apparent functional differences have impeded the development of a unified model for PEX16 action. The only reported pex16 mutant in plants, the Arabidopsis shrunken seed1 mutant, is inviable, complicating analysis of PEX16 function after embryogenesis. Here, we characterized two viable Arabidopsis pex16 alleles that accumulate negligible PEX16 protein levels. Both mutants displayed impaired peroxisome function − slowed consumption of stored oil bodies, decreased import of matrix proteins, and increased peroxisome size. Moreover, one pex16 allele exhibited reduced growth that could be alleviated by an external fixed carbon source, decreased responsiveness to peroxisomally processed hormone precursors, and worsened or improved peroxisome function in combination with other pex mutants. Because the mutations impact different regions of the PEX16 gene, these viable pex16 alleles allow assessment of the importance of Arabidopsis PEX16 and its functional domains. Abstract : Peroxisomes are essential oxidative organelles, and PEX16 is implicated in both peroxisome formation and membrane protein targeting. We characterized two Arabidopsis pex16 mutants with increased peroxisome size, decreased protein import into the organelle, and slowed utilization of stored fats. These viable pex16 mutants will facilitate further elucidation of peroxisome biogenesis.